Strategi pemerintah Kota Tangerang dalam pengembangan taman tematik di Kota Tangerang - Tunnisah, Elma Rahmah; Cadith, Juliannes; ., Ismanto (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2021)
Green Open Space Arrangement in Indonesia has been regulated in Regulation of the Minister of The Home Affairs Number 1 of 2017 concerning Green Open Space Arrangement of Urban Areas. The ideal areas of green open space are at least 20% of the urban area. Tangerang city is one of the cities located in Banten Province. To fill the green open space of urban areas, Tangerang City has several programs to develop the environment, one of which is Thematic Park. However, the availability of thematic parks has not been evenly distributed in tangerang city. A lack of facilities in the thematic park also utilization and maintenance have not been optimal. This research was conducted to find out and provide alternative strategies in the framework of the development of Thematic Parks in Tangerang City. The theory used SWOT analysis techniques. This study used a qualitative method with descriptive approach. The results of this study are known that the Tangerang City Government's Strategy in Thematic Park Development in Tangerang City has not been optimal and need an improvement, such as utilizing thematic parks as an alternative tourist destination, conducting sustainable cooperation between stakeholders, and inviting the public to participate in the development of thematic parks.